The mono-ADP-ribosyltransferase ARTD10 regulates the voltage-gated K(+) channel Kv1.1 through protein kinase C delta - Tian, Yuemin (BMC Biol, 2020)
BACKGROUND: ADP-ribosylation is a ubiquitous post-translational modification that involves both mono- and poly-ADP-ribosylation. ARTD10, also known as PARP10, mediates mono-ADP-ribosylation (MARylation) of substrate proteins. A previous screen identified protein kinase C delta (PKCδ) as a potential ARTD10 substrate, among several other kinases. The voltage-gated K(+) channel Kv1.1 constitutes one of the dominant Kv channels in neurons of the central nervous system and the inactivation properties of Kv1.1 are modulated by PKC. In this study, we addressed the role of ARTD10-PKCδ as a regulator of Kv1.1. RESULTS: We found that ARTD10 inhibited PKCδ, which increased Kv1.1 current amplitude and the proportion of the inactivating current component in HeLa cells, indicating that ARTD10 regulates Kv1.1 in living cells. An inhibitor of ARTD10, OUL35, significantly decreased peak amplitude together with the proportion of the inactivating current component of Kv1.1-containing channels in primary hippocampal neurons, demonstrating that the ARTD10-PKCδ signaling cascade regulates native Kv1.1. Moreover, we show that the pharmacological blockade of ARTD10 increases excitability of hippocampal neurons. CONCLUSIONS: Our results, for the first time, suggest that MARylation by ARTD10 controls neuronal excitability.